2020
DOI: 10.3390/jcm9041128
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Neutrophil-To-Lymphocyte Ratio and Platelet-To-Lymphocyte Ratio for Renal Outcomes in Patients with Rapidly Progressive Glomerulonephritis

Abstract: Background: Rapidly progressive glomerulonephritis (RPGN) is a syndrome characterized by a rapid decline in renal function that often causes end-stage renal disease. Although it is important to predict renal outcome in RPGN before initiating immunosuppressive therapies, no simple prognostic indicator has been reported. The aim of this study was to investigate the associations of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) to renal outcomes in patients with RPGN. Methods: Forty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
16
2
Order By: Relevance
“…Recently, hematological parameters (Neutrophil-to-Lymphocyte ratio (NLR), Platelet-to-Lymphocyte ratio (PLR) and Lymphocyte-to-Monocyte ratio (LMR)) have come into use as markers of systemic inflammation. They have been reported to be highly sensitive measures of inflammation in the field of oncology (lung cancer, esophageal cancer, gastric cancer, and endometrial cancer), cardiology, nephrology, diabetes, infectious diseases, and autoimmune rheumatic diseases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Increased NLR and PLR have been reported to be associated with cancer [ 5 ], diabetes [ 7 ], and psoriasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, hematological parameters (Neutrophil-to-Lymphocyte ratio (NLR), Platelet-to-Lymphocyte ratio (PLR) and Lymphocyte-to-Monocyte ratio (LMR)) have come into use as markers of systemic inflammation. They have been reported to be highly sensitive measures of inflammation in the field of oncology (lung cancer, esophageal cancer, gastric cancer, and endometrial cancer), cardiology, nephrology, diabetes, infectious diseases, and autoimmune rheumatic diseases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Increased NLR and PLR have been reported to be associated with cancer [ 5 ], diabetes [ 7 ], and psoriasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…LMR has been reported as a biomarker for infectious diseases, as a result of the balance between effector and host [ 1 ]. Elevated NLR was found as an independent predictor for in-hospital and long-term mortality in patients with acute heart failure [ 8 ], and NLR and PLR are candidates for predicting renal outcomes in patients with rapidly progressive glomerulonephritis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we showed that the NLR increased in the acute phase after ESD. The NLR is reported to be a marker of systemic inflammation, tumour stage, and histological type of gastrointestinal carcinoma 20 22 . WBC and neutrophils are regulated by TNF-α, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are representative blood markers of the systemic inflammatory response [ 4 ] and high NLR/PLR have been shown to be significantly associated with poor prognosis in a variety of malignancies [ 5 , 6 , 7 , 8 ]. Additionally, a close relationship between the systemic inflammatory response and tumor progression has been demonstrated in some types of cancers [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%